Cyclodextrin glycosyltransferase immobilization on functionalized graphene nanoplatelets for enhanced cyclodextrin production - Babatunde A. Ogunbadejo; Sulaiman Al-Zuhair (PLoS ONE, 2025)
Immobilization of enzyme on functionalized nanomaterials offers a promising strategy for enhancing enzyme stability, reusability, and activity in a variety of industrial applications. In this study, graphene nanoplatelets (GNPs) were functionalized with ethanolamine, 3-aminopropyltrimethoxysilane (APTMS), and 3-mercaptopropyltrimethoxysilane (MPTMS) to provide an efficient support for cyclodextrin glycosyltransferase (CGTase) immobilization. Thermogravimetric analysis (TGA) verified the successful incorporation of functional groups, including amine and thiol groups, and ethanolamine-functionalized GNPs showing the highest grafting levels. The maximum starch conversions observed with the functionalized supports were 21% for APTMS-functionalized GNP, 11% for ethanolamine-functionalized GNP and 7% for MPTMS-functionalized GNP. After 16 hours of continuous operation, ethanolamine- and APTMS-functionalized GNP retained 94% of their initial activity, while MPTMS-functionalized GNP maintained 86% residual activity at the end of the operation. Production rate of cyclodextrin reached 171 mg/g/hr for GNP-Ethanolamine, 185 mg/g/hr for GNP-APTMS and 90 mg/g/hr for GNP-MPTMS per gram of immobilized CGTase. This study showed that functionalized GNP exhibited better catalytic performance and good stability during cyclodextrin synthesis, hence, they demonstrate strong potential for developing commercial biocatalyst, paving the way for further advancements in using GNP-based supports in CGTase immobilization.